Unveiling the neuroprotective potential of dietary polysaccharides: a systematic review - Guo, Rui; Pang, Jingxi; Zhao, Junhe; Xiao, Xiao; Li, Jing; Li, Jingmeng; Wang, Wenxiu; Zhou, Shuang; Zhao, Yu; Zhang, Zilong; Chen, Hongwang; Yuan, Tian; et al. (Frontiers in Nutrition, 2023)
Central nervous system (CNS) disorders present a growing and costly global health challenge, accounting for over 11% of the diseases burden in high-income countries. Despite current treatments, patients often experience persistent symptoms that significantly affect their quality of life. Dietary polysaccharides have garnered attention for their potential as interventions for CNS disorders due to their diverse mechanisms of action, including antioxidant, anti-inflammatory, and neuroprotective effects. Through an analysis of research articles published between January 5 2013 and August 30 2023, encompassing the intervention effects of dietary polysaccharides on Alzheimer's disease, Parkinson's disease, depression, anxiety disorders, autism spectrum disorder, epilepsy, and stroke, we have conducted a comprehensive review with the aim of elucidating the role and mechanisms of dietary polysaccharides in various CNS diseases, spanning neurodegenerative, psychiatric, neurodevelopmental disorders, and neurological dysfunctions. At least four categories of mechanistic bases are included in the dietary polysaccharides' intervention against CNS disease, which involves oxidative stress reduction, neuronal production, metabolic regulation, and gut barrier integrity. Notably, the ability of dietary polysaccharides to resist oxidation and modulate gut microbiota not only helps to curb the development of these diseases at an early stage, but also holds promise for the development of novel therapeutic agents for CNS diseases. In conclusion, this comprehensive review strives to advance therapeutic